CHARACTERISTICS OF KEY FACTORS AFFECTING THE QUALITY OF FIXATION AND DURABILITY OF THE FUNCTIONING OF ARTIFICIAL CROWNS - N. O. Gevkaluk; V. R. Machogan (Eastern Ukrainian Medical Journal, 2019)
Introduction. Odontopreparation is an integral step in orthopedic dental treatment with non-removable orthopedic constructions. Correctly performed this stage in the treatment of artificial crowns is a guarantee of the quality of orthopedic treatment. Ensuring a stable geometry of the stump, a ledge of sufficient width on the abutment and the absence of defects on its surface, the clarity of the preparation margin and the correct ratio with marginal periodontal tissues are the most significant criteria for the quality of the intervention. In addition, the quality of the odontopreparation of the orthopedic profile is influenced by the clarity of adherence to the selected algorithm of preparation and the properties of the rotary tool used. The available literature data indicate numerous deviations in the practice of dentistry from the recommended methodology of odontopreparation, which can be explained by the relatively high frequency of complications of treatment with non-removable orthopedic structures. The purpose of the article is to analyze the key factors affecting the quality of fixation and the durability of the functioning of artificial crowns, based on an assessment of the basic principles of odontopreparation for this type of orthopedic structures and the reaction of periodontal tissues based on an analytical review of the literature. Materials and methods. The article presents the data of the literature review on the main factors that are of great importance as the fixation and durability of the functioning of artificial crowns on the stumps of dissected teeth while observing step-by-step odontopreparation algorithms with provision of proper functional and desired aesthetic requirements without negative influence on the condition of the tissue. Conclusion. Based on the analysis of literary sources, it was concluded that the key factors affecting the quality of the formation of the tooth stump to be prosthetized, subject to step-by-step odontoperational algorithms with the creation of conditions for high-quality fixation and durability of the functioning of the artificial crown, ensuring the proper functional and desired aesthetic requirements without negative impact periodontal tissues can significantly reduce the manifestation of unwanted complications, and as a result to increase the effectiveness of prosthetics with artificial crowns.